150 ways teens can make a difference - Salzman, Marian (Peterson's H.S. series, 1991)
Teenagers discuss the rewarding and sometimes frustrating experiences of being a volunteer, including their commitment and accomplishments, parental support, and how they incorporate volunteer activities into their busy high school schedules.